INDIKATOR USER SATISFACTION DALAM APLIKASI E-LECTURE (VIDEO PEER-EVALUATION PADA ONLINE CBL) - Diah Aryani; Muhamad Yusup; Ilamsyah Ilamsyah (CCIT Journal, 2018)
Currently, the learning process of more interactive e-learning method in college becomes a necessity, but the current e-learning learning method still uses the Teacher Centred Learning (TCL) approach. Of course, this TCL approach is less relevant for its high use of curriculum that refers to the National Qualification Framework (KKNI) so it is necessary to integrate into a more active and interactive approach that is Collaborative Learning (CbL) approach. CbL's approach to the implementation of the student becomes more active in developing knowledge and learning skills so as to create a more cooperative, supportive and cooperative classroom climate. Implementation of e-learning with Cbl approach, students in collaboration with their groups and exposing presentation materials online in the form of presentation videos by each group and other groups directly assess the presentation to each member of the presentation group. Usability analysis of video peer evaluation application on CbL online using user satisfaction focused on usability aspect analysis where user acting as Video Peer-Evaluation application user. In this research, the method of analysis using Structural Equation Modeling (SEM) or structural equation model is a multivariate analysis that is used to analyze relationships between variables in a complex manner. the main requirement of using SEM is to design hypothesis model by using structural model and measurement model in the form of path diagram. It is hoped that this research can remind the satisfaction that can be used to measure the success of Video Peer Evoluation application in online colaborative learning